EVALUASI TINGKAT KEBERHASILAN TANAMAN MERANTI MERAH (Shorea leprosula Miq) DI AREAL MINIATUR HUTAN HUJAN TROPIS (MH2T) PROVINSI KALIMANTAN SELATAN - Stefanus Debrito Heka; Setia Budi Peran; Sulaiman Bakri (Jurnal Sylva Scienteae, 2021)
The purpose of this study was to analyze the growth condition of red meranti plants and classify the succes rate of red meranti plants. The method used in the sturated sampling method (census), data collection is carried out on all red meranti plants in the measuring block by observing and measuring the plant height and diameter parameters directly. The result showed that the health conditions of red meranti plants consisted of 23,46% healthy plants, 57,21% unhealthy and 19,34% languorous with a plant growth percentage of 40,59% smaller than the percentage of dead plants of 59,41%. The success rate of red meranti plants is 40%, so classification of red meranti planting is a low criterion so that intensive maintenance is needed to achieve the desired results.Keywords: Red Meranti; Evaluation; Success rate